Saber sobre sua origem: reações e mudanças ocorridas na vida do filho adotivo - Souza, Marciana da Silva (2014)
The adoption issue is being debated currently in the media (articles, interviews, novels, movies), colleges (monographs, dissertations, theses, books, scientific events), and society (enactment of laws, formation of support groups and also a national association of these groups). Efforts have been made to spread a new culture of adoption, which prioritizes children s rights and needs. Among these, first of all, the right to know about their origin. Adoption has, as the most important of its principles, child s integration in new families, which gives them the possibility of a new identity reconstruction, once they have the knowledge about their origin, consequently supporting a new pleasant family interaction. Their adaptation in a new place, purpose the establishment of new family bands, which is going to need different and new emotional components: love, affection, attention, commitment and above all of it, respect to their progress history. This research has a general objective: to understand and identify, on adopted adults perspective, if there were changes, and what those changes were, what happened in their lives after that they had knowledge about their origin. Specifically the intention is: to understand how this knowledge was taken, and the importance it has in the adoptees identity organization; to comprehend how adoptees started to perceive their new parents and themselves; what their position when it comes to myths, fears, beliefs and prejudices is, permeating the social imaginary. To achieve the proposed objective, we opted for a qualitative methodology. Eight adults were interviewed, both genders, those who had knowledge about their origin, and the context was analyzed based on the thematic technique of analysis content. Results indicate that: 1) although varied the age that they became aware of their origin, the participants consider essential that knowledge and propose that every adopted child has this right; 2) motivations for child adopting vary, prevailing financial difficulties; 3) there are different reactions between those who early knew their condition and those who got this piece of information when they were teenagers; 4) despite losses, the majority was satisfied with their adoptive family, indicating affection feelings, gratitude and recognition of their importance for survival and formation of their personality; 5) they were against prejudice and myths that pervade the condition of adoptive person; It s expected to contribute, aiming to highlight the issue, seeking to stimulate a greater awareness on the part of society to overcome the myths and prejudices that still roam the adoption.